Growth after the Crisis - Rodrik, Dani (World Bank, Washington, DC, 2017)
How hospitable will the global environment be for economic growth in the developing world as we come out of the present financial crisis? The answer depends on how well the author manage the following tension. On the one hand, global macro stability requires that we prevent external imbalances from getting too large. On the other hand, growth in poor nations requires that the world economy be able to absorb a rapid increase in the supply of tradable produced in the developing world. It is possible to render these two requirements compatible, but doing so requires greater use of explicit industrial policies in developing countries, which have the potential of encouraging of modern tradable activities without spilling over into trade surpluses. The 'price' to be paid for greater discipline on real exchange rates and external imbalances is greater use (and permissiveness) towards industrial polices.